2000
DOI: 10.1143/jjap.39.6277
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Ablation of Metals and Silicon by Femtosecond Laser Pulses for Application to Surface Analysis

Abstract: For the purpose of thin-layer surface analysis, comparison of laser ablation by 24 ns ArF laser pulses at 193 nm and that by 150 fs Ti:sapphire laser pulses at 780 nm for samples ranging from metals to semiconductors is reported. In contrast to nanosecond laser pulses, the ablation threshold for femtosecond laser pulses could be reduced significantly. In particular, the threshold for a Si sample was reduced to about one order of magnitude, and an ablation rate of 0.48 nm/shot was obtained at 5% above the thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Preliminary research using femtosecond lasers for analytical spectroscopy has only recently been reported [28,29].…”
Section: Intrinsic Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary research using femtosecond lasers for analytical spectroscopy has only recently been reported [28,29].…”
Section: Intrinsic Fractionationmentioning
confidence: 99%
“…Femtosecond laser pulses might be favorable for providing reduced fractionation because of minimal thermal effect [27]. Preliminary studies using femtosecond lasers for analytical spectroscopy have been reported recently [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Ablation of less than 10 nm per shot has been demonstrated with fs-laser (Nolte et al, 1997;Kim et al, 2000; and that is close to depth resolutions of the best established in-depth analysis techniques, such as secondary ion mass spectrometry (SIMS) and glow discharge-mass spectrometry (GD-MS), typically 5-10 nm (Bubert & Jenett, 2001). At the same time, those techniques have different lateral resolutions, in the range from 100 nm (SIMS) to a few mm (GD-MS).…”
Section: A In-depth Profilingmentioning
confidence: 99%
“…The best results of LA in-depth profiling can be expected at the ultra-high vacuum (UHV) conditions that are necessary for most of the established techniques (Schütze et al, 1995;Kim et al, 2000;Garcia et al, 2003); however, laser ablation in-depth profiling could be performed also in the presence of a noble gas or under atmospheric conditions (Anderson et al, 1995;Vadillo & Laserna, 1997;Bleiner et al, 2000;Plotnikov et al, 2001). That possibility is significant for many applications where fast, on-line analysis is needed, and therefore UHV should be avoided.…”
Section: A In-depth Profilingmentioning
confidence: 99%
“…Based on interactions with the physics community, the PI believes that femtosecond laser pulses will provide an ideal environment for matrix independence because of the minimization of thermal effects. Preliminary research using femtosecond lasers for analytical spectroscopy has only recently been reported (48,49). Research by the physics community has demonstrated that femtosecond lasers provide a different particle size distribution that that from longer-pulsed lasers, although a comparison of the particle chemistry has not been reported.…”
Section: Particle Generation From Laser Ablation Processesmentioning
confidence: 99%